Inflammatory bowel disease and colon cancer. - Jawad, N; Direkze, N; Leedham, S (2011)
The inflammatory bowel diseases (IBD); Crohn's and Ulcerative colitis, result from an altered host response to intestinal flora. Recurrent inflammation with ulceration and tissue restitution confers an increased risk of cancer in both UC and Crohns, and genome wide searches have identified a number of disease susceptibility alleles. The carcinogenesis pathway in colitis-associated colorectal cancer (CACRC) is less clearly understood than it's sporadic counterpart. Clonal ordering experiments have indicated the order and timing of chromosomal instability and common genetic mutations. Epigenetic changes such as DNA methylation and histone modification are thought to play an increasingly important role in inflammation induced carcinogenesis. Clonal expansion of procarcinogenic mutations can lead to large fields of mutant tissue from which colitis associated cancers can arise (field cancerisation). Endoscopic screening is the mainstay of surveillance in high-risk patients although the development of appropriate, clinically applicable biomarkers remains a research priority. Despite the expanding field of biological therapy in inflammatory bowel disease the ASA compounds remain the best-studied and most efficacious chemopreventive agents. Colitis associated CRC appears to have a different aetiology, carcinogenesis pathway and clinical course to its sporadic counterpart. Further research including long-term follow up of patient cohorts taking biological therapies will improve the detection and treatment of these important, inflammation-induced malignancies.